Low back pain in adolescents and association with sociodemographic factors, electronic devices, physical activity and mental health - Thiago Paulo Frascareli Bento; Guilherme Porfirio Cornelio; Priscila de Oliveira Perrucini; Sandra Fiorelli Almeida Penteado Simeão; Marta Helena Souza de Conti; Alberto de Vitta (Brazilian Society of Pediatrics, 2020)
Objectives: To determine the prevalence of low back pain and to analyze the association with the individual, sociodemographic variables, electronic devices, habitual practice of physical activity, and mental health problems. Methods: Cross‐sectional study with 1,628 students in public schools in the city of Bauru, SP, Brazil. The following data were collected: 1. demographic and socioeconomic aspects; 2. Use of electronic devices; 3. habitual physical activity level (Baecke); 3. mental health (SDQ). 4. low back pain (Nordic Questionnaire). Descriptive analyzes and bivariate and multivariate logistic regression were used. Results: The overall prevalence of low back pain was 46.7% (95% CI: 44.27 to 49.11); men showed a prevalence of 42.0% (95% CI: 36.63 to 43.41) and women 58.0% (95% CI: 49.73 to 56.51), a statistically significant difference. The variables associated with pain in the low back region were: female gender (PR = 1.70), daily TV use for more than 3 hours (PR = 1.17), use of laptop computer (PR = 1.40), use of the cell phone in the supine position (PR = 1.23), use of the cell phone in semi‐supine position (PR = 1.49), daily cell phone use for more than 3 hours (PR = 1.36), use of tablet (PR = 1.67), daily tablet use for more than above 3 hours (PR = 1.46), and clinically important mental health problems (PR = 2.62). Conclusion: There is a high prevalence of low back pain in high school students and striking association with female sex, electronic devices, and mental health problems. Resumo: Objetivos: Determinar a prevalência de lombalgia e analisar a associação com variáveis individuais e sociodemográficas, dispositivos eletrônicos, prática habitual de atividade física e problemas de saúde mental. Métodos: Estudo transversal com 1.628 alunos matriculados em escolas públicas na cidade de Bauru/SP. Para a coleta de dados: 1. aspectos demográficos e socioeconômicos; 2. dispositivos eletrônicos; 3. nível habitual de atividade física (Baecke); 3. saúde mental (SDQ); 4. Lombalgia (Questionário Nórdico). Foram usadas análises descritivas e de regressão logística bivariada e multivariada. Resultados: A prevalência geral de lombalgia foi 46,7% (IC de 95%: 44,27 a 49,11), os homens mostraram uma prevalência de 42,0% (IC de 95%: 36,63 a 43,41) e as mulheres mostraram uma prevalência de 58,0% (IC de 95%: 49,73 a 56,51), com diferença significativa. As variáveis associadas a dor na região lombar inferior foram: sexo feminino (RP = 1,70), tempo de uso de TV acima de 3 horas por dia (RP = 1,17), uso de notebook (RP = 1,40), uso de celular na posição supina (RP = 1,23), uso de celular na posição semissupina (RP = 1,49), tempo de uso de celular acima de 3 horas por dia (RP = 1,36), uso de tablet (RP = 1,67), tempo de uso de tablet acima de 3 horas por dia (RP = 1,46) e problemas de saúde mental clinicamente importantes (RP = 2,62). Conclusão: Há alta prevalência de lombalgia em alunos do ensino médio e forte associação ao sexo feminino, dispositivos eletrônicos e problemas de saúde mental.